관측 행렬 산출 기법 별 DGNSS-CP 성능 비교 - 신동현; Dong-hyun Shin; 임철순; Cheol-soon Lim; 석효정; Hyo-jeong Seok; 윤동환; Dong-hwan Yoon; 박병운; Byungwoon Park (한국항행학회논문지, 2016)
저가형 GNSS (global navigation satellite system) 수신 모듈에 DGNSS (differential GNSS) 서비스를 적용하기 위한 방안으로 거리 영역의 보정정보를 위치 영역으로 투영한 후, stand-alone으로 산출한 위치에 적용하는 DGNSS-CP 방식이 제안된 바 있다. DGNSS-CP 를 상용 수신기 또는 휴대폰에 적용하기 위해서는 항법 방정식의 관측행렬을 이용하여 위치영역 투영 방정식을 구성하므로, 각 위성의 시선벡터를 산출하여야 한다. GNSS 항법 메시지, 배치 정보 등이 시선벡터 산출을 위하여 사용되는데, 각 방법에 따라 정확도와 연산량 등의 성능에 차이가 발생한다. 본 연구에서는 제시된 두 가지 시선벡터 산출 방식에 따라 DGNSS-CP 의 성능에 어떠한 영향을 끼치는지 확인하기 위하여, Septentrio PolaRx4 Pro 수신기에서 stand-alone mode 로 저장된 데이터에 해당 알고리즘을 적용하였고, 배치 정보를 사용하는 방법이 궤도정보를 사용하는 방법에 비해 정확도 면에서는 그 성능이 RMS (root mean square) 0.1 m 가량 저하되는 반면, 연산량은 약 1/15수준으로 줄일 수 있음을 확인하였다. Several low-cost global navigation satellite system (GNSS) receivers do not support general range-domain correction, and DGNSS-CP (differential GNSS) method had been suggested to solve this problem. It improves its position accuracy by projecting range-domain corrections to the position-domain and then differentiating the stand-alone position by the projected correction. To project the range-domain correction, line-of-sight vectors from the receiver to each satellite should be calculated. The line-of-sight vectors can be obtained from GNSS broadcast ephemeris data or satellite direction information, and this paper shows positioning performance for the two methods. Stand-alone positioning result provided from Septentrio PolaRx4 Pro receiver was used to show the difference. The satellite direction information can reduce the computing load for the DGNSS-CP by 1/15, even though its root mean square(RMS) of position error is bigger than that of ephemeris data by 0.1m.